Kiprah Lembaga Pesantren Dalam Meningkatkan Pendidikan Indonesia - Santoso, Achmad Erwin; Suhirman, Suhirman; Untung, Slamet (LPPM Institut Pendidikan Nusantara Global, 2025)
Islamic boarding school institutions have long been active in educating the Indonesian nation. This work is not only in the religious field, but also in the educational field. The discussion was about the important role of Islamic boarding school institutions in improving education in Indonesia. This research aims to find out about the history of Islamic boarding school education, the role of Islamic boarding schools in educating the nation, the contribution of Islamic boarding schools in improving the quality of education in Indonesia, and the weaknesses of Islamic boarding schools in the advancement of science. This research uses qualitative methods by relying on library research, namely collecting data from books, articles and other sources relevant to the research topic. The results of this research are that Islamic boarding schools have an important and strategic role in improving the quality of education in Indonesia. The role of Islamic boarding schools is not only in the aspect of religious education, but also in the aspect of general education and developing national character.